Personal Hygiene Pada Makanan Siap Saji di Desa Latta Kecamatan Teluk Ambon Baguala - Rusdin Waly (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Because the human body can also be a source of pollution if it is not kept clean, personal hygiene can have an impact on food contamination for a number of reasons, including the cleanliness of dining utensils. Food equipment that does not adhere to health regulations is another source of contamination, in addition to food and water sources. Regulation No. 1096/Menkes/SK/VI/2011, issued by the Minister of Health of the Republic of Indonesia, outlines the hygienic and sanitary standards for food services in that country.The research problem, which is the personal hygiene of fast food meals in Latta Village, Teluk Ambon Baguala District, can be stated based on the preceding description.Goal. To quickly learn about personal hygieneThrough observation and interviews, this kind of study is descriptive. Twenty-two fast food vendors made up the study's population. Five (five) fast food vendors in Latta Village made up the sample. According to the findings of the study, five checks on traders I, II, III, IV, and V with the criteria do not satisfy the requirements in line with Minister of Health Regulation No. 1096/Menkes/Per/VI/2011, specifically 0 CFU. According to the findings, five food handlers in Latta Village, Teluk Ambon Baguala District, did not adhere to the standards for personal cleanliness. Five food handlers in Latta Village, Teluk Ambon Baguala District, had personal hygiene that did not meet the standards, while five of these samples did.